2009
DOI: 10.1111/j.1399-5448.2009.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of vitamin D in North Indian children with newly diagnosed type 1 diabetes

Abstract: These results suggest that vitamin D levels are low at the onset of T1D, and they strongly support the need for further clinical studies to prospectively evaluate the effect of vitamin D supplementation on T1D rates in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
76
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 34 publications
12
76
4
1
Order By: Relevance
“…This is consistent with two previous case-control studies of serum 25(OH)D [8,9], but not a third [10]. An inverse association between serum 25(OH)D and risk of insulin-requiring diabetes was present in the same direction and was statistically significant in all race groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with two previous case-control studies of serum 25(OH)D [8,9], but not a third [10]. An inverse association between serum 25(OH)D and risk of insulin-requiring diabetes was present in the same direction and was statistically significant in all race groups.…”
Section: Discussionsupporting
confidence: 81%
“…These studies depended on self-reported questionnaires, which may have limited their validity. Two ordinary case-control studies found that serum 25(OH)D was inversely associated with risk of insulin-requiring diabetes [8,9], but a third study found no association [10].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Shellhaas et al demonstrated female gender to be significantly associated with vitamin D deficiency in their study on epileptic children which was attributed to biological/ behavioral differences. 4 Vitamin D levels decreased progressively with age (p=0.034) in our data, a finding not studied in many of the Indian studies. A study done by Absoud and et al found that vitamin D levels decreased with age in both sexes and confirmed a previously under-recognized risk of VDI in adolescents.…”
Section: Discussionsupporting
confidence: 66%
“…In our study 89.1% of children had vitamin D levels less than 30 ng/ml. In this category about 10.9% were severely deficient (SD), 70.8% were deficient (D) and 7.4% were insufficient (I) in vitamin D. A study by Shellhaas 4 showed only 25% of children to have vitamin D levels in sufficient range in children with epilepsy. Our study revealed a prevalence of 89% which may be higher as compared to studies on neurological illnesses internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence varied from as high as 90.60% with a vitamin D cutoff value of < 30 ng/ mL in Qatar (6), to as low as 15% with a vitamin D cutoff value of < 20 ng/mL at Joslin's diabetes center (9), and intermediate prevalence of 54% with a vitamin D cutoff value of < 32 ng/mL in DIASS study (8). In one north Indian study, 58% children with T1DM aged between 6 and 12 year were vitamin D-deficient as compared with only 32% in the control group (25). In our study 25(OH)D was significantly lower (mean ±SD of 7.88 ± 1.20 ng/mL) in patients, compared with 16.64 ± 7.83 ng/mL in the controls.…”
Section: Discussionmentioning
confidence: 99%